Unilateral Headache Status after Intra-Aortic Balloon Pump Placement - Garret M. Weber; Alan L. Gass; Shalvi B. Parikh (Case Reports in Medicine)
Introduction. Intra-aortic balloon pump (IABP) counterpulsation is a catheter-based treatment for coronary artery disease and decompensated heart failure to increase coronary blood flow and improve cardiac output. IABP is generally well tolerated, and complications are usually related to peripheral vasculature or red blood cell and platelet consumption. The usual insertion site via femoral artery renders the patient bedbound. Recently, axillary artery has been used in patients with atherosclerotic peripheral vascular disease and documented small arteries or in those awaiting transplant to ensure ambulation and prevent deconditioning. Case Report. We present a patient with ischemic cardiomyopathy and severe left ventricular dysfunction, awaiting Orthotropic Heart Transplant. His worsening intractable angina and dyspnea necessitated IABP placement via left axillary artery, significantly improving his condition. He subsequently experienced migraine-type persistent unilateral headache refractory to standard pain management. Multiple strategies were utilized to treat his pain, but the patient insisted that his pain commenced after IABP placement. Ultimately, the removal of the pump led to complete resolution with no recurrence. Conclusion. The authors hypothesize that the unilaterally directed blood flow and direct increase in cerebral perfusion from the intra-aortic balloon pump may have caused vasodilation of the extracranial arteries, leading to a persistent and debilitating headache in this susceptible patient.